Penerapan Algoritma Evolusi Dengan Metode Generation Replacement Pada Aplikasi Penjadwalan Mata Kuliah - Syarif, Adi Chandra; Gunawan, Farid Hartono (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
Course scheduling problem belongs to the category of NP - hard (Non - deterministic polynomial - time complex). The complexity of solving course scheduling problems give an indication to the limits of the constraints to the problem. The application of evolutionary algorithms with Generation Replacement Methods on Course scheduling problem (Case Study of the University of Atma Jaya Makassar) can give an indication on the problem of scheduling constraints that limit each faklutas at Atma Jaya University, Makassar. Simulation results showed that scheduling constraints limit in any faculty at the University of Atma jaya Makassar depends on the size of the population space and the number of genes that are raised to fill the space where the population or chromosome problem complexity increases with introduction of restrictions on the scheduling of such sessions , space , semester and faculty and computational complexity of the problem requires greater resources in line with the increasing restrictions being introduced